INTEGRATING SPIRITUALITY IN DEVELOPMENT OF HOLISTIC CARDIAC REHABILITATION MODULE FOR MUSLIM PATIENTS USING THE MODIFIED DELPHI TECHNIQUE - Norizam; Asrenee; Zurkurnai; Hafiz (Jurnal Penyelidikan Sains Sosial, 2020)
About 15% - 20% of coronary heart disease (CHD) patients are at risk for anxiety and depression. This increases the risk of morbidity and mortality also affects treatment outcomes. Empirical support from previous studies show standard cardiac rehabilitation program should include spiritual component to ease psychological ailment. The purpose of this study is to develop The Holistic Cardiac Rehabilitation (HCR) program using Modified Delphi Technique (MDT). Method of these two round modified Delphi technique study involved 16 expert panels. Consensus was obtained on the content of the HCR module. The module consisted the components of health education (CHD and diet, anxiety and depression), physical rehabilitation and spiritual. The consensus for this study is defined by a 75% of expert panels response of a minimum mean score of 3 on the Likert scale for each component of MDT. The result from final round of MDT shows the mean score of 3.9 (98%) for health education (CHD), 3.5 (88%) for health education (anxiety and depression), 3.8 (95%) for health education (diet), 3.5 (88%) for physical rehabilitation and 3.8 (95%) for spiritual. The results of this study show that the expert panels give their consensus for this module through MDT successfully.